Bull semen harvesting: a new area of economic interest for dairy farmers - Bisla, Amarjeet; Yadav, Vinay; Srivastava, N; Ghosh, S K (Indian Farming, 2018)
This article highlighted the importance of bull semen harvesting as a new area of economic interest for the farmers. Farmers can earn handsome money by the way of semen harvesting on the minimum cost of the rearing of a bull. On a conservative estimate, a farmer can earn around Rupees 1 lakh on a year basis from a single bull through semen harvesting.